Предмет: Математика, автор: mirasmasalim864

А) (15 1_ 2 - 2 3_8) - (5 5_6+6 3_4) +(10 2_3-5 5_8) з) (20-19 3_4) +(17 3_4-17)+(2 2_1-17_24). ​

Ответы

Автор ответа: sirykmasha201252
0

Відповідь:

А) (15 1_2 - 2 3_8) - (5 5_6 + 6 3_4) + (10 2_3 - 5 5_8)

= 15 1_2 - 2 3_8 - (5 5_6 + 6 3_4) + (10 2_3 - 5 5_8)

= 15 1_2 - 2 3_8 - 5 5_6 - 6 3_4 + 10 2_3 - 5 5_8

= (15 - 2 - 5 + 10) + (1_2 - 3_8 - 5_6 - 3_4 + 2_3 - 5_8)

= (18) + (-7_4)

= 18 - 7_4

= 17 9_4

з) (20 - 19 3_4) + (17 3_4 - 17) + (2 2_1 - 17_24)

= (20 - 19 3_4) + (17 3_4 - 17) + (2 2_1 - (17 + 24))

= (20 - 19) + (3_4 - 17) + (2_1 - (41))

= (1) + (-13_4) + (-39)

= 1 -13_4 -39

= -38 11_4

Покрокове пояснення:

Похожие вопросы